REE, Rb-Sr and Pb isotopic characteristics of the Yamato-791197 meteorite: Evidence for a lunar highland origin - Nakamura,Noboru; Unruh,Daniel M.; Tatsumoto,Mitsunobu (1986)
P(論文) Rb-Sr systematics, Pb isotopic composition, and REE, Ba, Sr, Rb, K, Ca, Mg and Fe concentration analyses were carried out for matrix and clasts from the anorthositic breccia, Yamato-791197 meteorite. Major and trace element abundances in the matrix and clasts are similar to those in lunar anorthositic rocks. The estimated initial ^<87>Sr/^<86>Sr ratio for two anorthositic clasts at 4.55 b. y. is similar to the lunar initial ratio (LUNI) and lower than BABI, which is consistent with lunar origin of the meteorite. The LUNI model ages for two split of the matrix are 4.0 and 4.1 b. y., indicating that the Rb-Sr system of the matrix was perturbed by a late event. One matrix sample shows very high ^<207>Pb/^<204>Pb (=118-129) and high ^<207>Pb/^<206>Pb (=1.05) ratios which are characteristic of lunar anorthosite Pb, and which are unique among solar system samples thus far analyzed. One anorthositic clast shows a Pb isotopic composition similar to that of lunar soils or mare basalts. Consequently, the Pb data provide strong evidence for a lunar origin of the meteorite. Chemical compositions including high Pb concentrations together with very low ^<87>Sr/^<66>Sr ratios and unique Pb isotopic compositions suggest that the meteorite represents an unsampled type of lunar highland rock which may have formed at 4.55 b. y. and brecciated at <4.0 b. y. departmental bulletin paper